The Implementation of Collaborative Strategic Reading in Teaching Reading Comprehension at SMK Nurul Islam Pongangan - Rohmah, Aljunda Intana Inayatur (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2025)
Students have difficulties in understanding an English text because they lacked vocabulary mastery, which made them lazy to read and feel bored in the learning process. In the teaching and learning process, teachers need methods to make the lesson easier. Collaborative Strategy Reading is an excellent teaching technique to teach students to navigate comprehension and build vocabulary as well as work together cooperatively. Klingner and Vaughn (1998) in Nurhayati (2015) state that Collaborative Strategic Reading is an excellent strategy for teaching students reading comprehension and building vocabulary and also working together cooperatively. The purpose of this study is to determine the use of Collaborative Strategic Reading (CSR) in reading comprehension instruction, students' classroom responses to the use of CSR methods, and the strengths and weaknesses of CSR in reading comprehension instruction due to the lack of interest in reading activities among students in reading classes. The design of this research is a case study qualitative. In this study, the researcher used observation, interview and documentation to get the data. The result of this study showed that the teacher used three-phase technique. It consists of pre activity, while activity and post activity. The strength Collaborative Strategic Reading is an interesting strategy for teaching English to students because in CSR students are taught to learn cooperatively so that students are free to express their opinions and ask questions, which include previewing, click and clunk, get the gist and wrap up through cooperative work. In the process of using CSR, students showed positive attitudes and actively participated during the implementation of CSR. The weakness of using CSR is it takes quite a long time compared to normal learning because they have to form groups and discuss to come up with accurate answers.